The effect of aerosol suction distance during brushing brackets of orthodontic patients on the presence of Streptococcus and Staphylococcus - Andi Triawan; Belladina Yusi Lasara (Majalah Kedokteran Gigi Indonesia, 2022)
Dentists are one of the professions most at risk of infection transmission because dental care potentially produces many infectious aerosols for bacterial transmission. Using personal protective equipment and aerosol suction that meets the standards for dentists is vital to prevent cross-infection in patients in practice. This study aims to determine the effect of aerosol suction distance on the orthodontic patient bracket brushing process on total plate number and the presence of Streptococcus and Staphylococcus on the dentist’s face shield. The method used is the swab method on the face shield used by dentists after brushing orthodontic patient brackets with variations in the distance of aerosol suction to the oral cavity of 10 cm, 15 cm, and 20 cm. After 2 x 24 hours of incubation, the total plate count was calculated, and Streptococcus and Staphylococcus were identified by analyzing the characteristics of the growing colonies and executing the catalase test. The results showed that the lowest total plate number found on a face shield with aerosol suction distance of 10 cm from the oral cavity, 1.23 ± 0.01 CFU/cm2. The one-way ANOVA test obtained a significance value of p < 0.05, concluding that the variation of the aerosol suction distance affects the total face shield plate number. The presence of bacteria on the face shield was negative for Streptococcus and positive for Staphylococcus.